The Role Of Mastermind Leader In Building Islamic Culture At Muhammadiyah Tanjung Redeb Senior High School - Rahmat Hidayatullah; Khamam Khosiin; Ahsan Hakim (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the role of the mastermind leader in developing Islamic school culture at SMA Muhammadiyah Tanjung Redeb. The study responds to the increasing need for educational leadership models that are not only managerial but also capable of designing, transforming, and sustaining Islamic values within school organizations. This research employed a qualitative case study approach. Data were collected through semi-structured interviews, observation, and document analysis involving the principal, vice principals, Islamic education teachers, teachers, and students. Data were analyzed using thematic analysis through the stages of data familiarization, coding, theme development, interpretation, and verification. The findings reveal that the mastermind leader plays five strategic roles: (1) as an Islamic cultural architect who formulates institutional vision, (2) as a value transformer who integrates Islamic principles into school practices, (3) as a moral role model who demonstrates exemplary leadership behavior, (4) as a mobilizer who develops collective participation through distributed leadership, and (5) as a sustainability builder who institutionalizes Islamic culture through continuous evaluation and regeneration. This study contributes to Islamic educational leadership literature by proposing the mastermind leader concept as an integrative framework combining transformational, instructional, distributed, strategic, and Islamic value-based leadership perspectives. The study implies that sustainable Islamic school culture requires visionary leadership supported by collaboration, institutional commitment, and value internalization.